PENGARUH LOKASI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN RUMAH PADA PT. RIZKY ADRI PERKASA - Ahyani Ahyani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to determine the effect of location and price on the decision to buy a house at PT. Rizky Adri Perkasa. The research methodology used is the Associative method. The population in this study were all home buyers at PT. Rizky Adri Perkasa using the Slovin formula obtained a sample of 166 respondents. The data analysis method used simple linear regression test, multiple linear regression, and correlation coefficient, coefficient of determination, partial t test and simultaneous F test. The results showed that: (1) There was an influence of location on the decision to buy a house at PT. Rizky Adri Perkasa this can be proven from a simple linear regression equation Y=26,151+0,420X1. The correlation value is 0.656 (strong). The value of the coefficient of determination is 43%. The value of tcount 11.118 > ttable 1.974 with a significance of 0.000 <0.05. (2) There is an influence between the price on the decision to buy a house at PT. Rizky Adri Perkasa, this can be proven from the simple linear regression equation Y=23,155+0,484X2. The correlation value is 0.709 (strong). The value of the coefficient of determination is 50.2%. The tcount is 12.867 > ttable 1.974 with a significance of 0.000 <0.05. (3) There is an influence between location and price on the decision to buy a house at PT. Rizky Adri Perkasa, this can be proven from the multiple linear regression equation Y=21,722+0,192X1+0,336X2. The correlation value is 0.738 (Strong). The value of the coefficient of determination is 54.5%.F value calculated is 97.583 > Ftable 3.90 with a significance level of 0.000 <0.05.